A Cognitive Semantic Study of Comforting in English and Arabic Religious Texts - Hameed, Hussain; Abdallah, Widad Ayid (جامعة بابل - كلية التربية للعلوم الإنسانية, 2023)
This study presents a cognitive semantic analysis of the comforting in English and Arabic religious texts on meaning construction in selected English and Arabic religious texts. The main questions that the study tries to answer are related to the functions of comforting expressions in religious texts, to the similarities and differences in interpreting comforting expressions involved in Quranic verses and the Bible. The study aims at identifying the functions of the comforting expressions and identifying the religious texts that has more comforting expressions that are found in English and Arabic religious texts, Providing an adequate knowledge for the comforting expressions based on both cognitive and semantic perspectives that appears in religious texts. Offering how religious texts can cognitively and semantically illustrate different perspectives to human beings through comforting expressions. Explaining different strategies utilized in interpreting the comforting expressions that are found in religious texts. In addition, the study examines the universality of Conceptual Metaphor Theory and the shared and culture specific conceptual metaphors in the comforting expressions under study. The study hypothesizes that Holy Quran has more comforting expressions than Biblical texts. Most of English and Arabic religious texts can cognitively and semantically discuss various perspectives to man based on comforting expressions.Different strategies of comforting expressions can be found in most of religious texts. The study also hypothesizes the significant role played by grammatical structures in understanding comforting by determining the kind of the conceptual integration network. To achieve the aims of the study and verify its hypotheses, a model based on the Conceptual Integration Theory and Conceptual Metaphor Theory has been adopted to analyze a sample of selected English and Arabic religious texts. The selected sample consists of 2 English religious texts and 2 Arabic religious texts. In both types of data, linguistic devices are resorted to when approaching religious texts in respect to the descriptive persuasive strategies. The macrostructures whereby comforting is included can be different between English and Arabic religious contexts due to the religious differences between these two types of data.
Keywords: النصوص الدينية -- الدلالات المعرفية -- الاستعارات المفاهيمية